Trying Leviathan: The Nineteenth-Century New York Court Case that Put the Whale and Challenged the Order of Nature - E. N. Anderson (Ethnobiology Letters, 2010)
Review of Trying Leviathan: The Nineteenth-Century New York Court Case that Put the Whale and Challenged the Order of Nature. D. Graham Burnett. 2007. Princeton University Press. Pp. 304 color plates, halftones, bibliography, index. $29.95(cloth). ISBN 9780691129501.